Effect of mulching and amelioration on growth and yield of groundnut on saline soil - Abdullah Taufiq; Andy Wijanarko; Afandi Kristiono (Brawijaya University, 2017)
Agricultural lands affected by salt facing complex problems associated with soil salinity and the toxicity effects of Na cation. Soil amelioration and mulching is an alternative to alleviate negative effect of salinity. Objective of research was to identify effective ameliorant, and effect of mulching in improving growth and yield of groundnut on saline soil. The research had been conducted on saline soil (soil EC 12 dS/m) in Lamongan during dry season of 2016, using Hypoma 2 cultivar. Treatments that consisted of two factors were arranged in a split plot design with three replicates. The main plot was mulching (without mulching and mulching with 3.5 t/ha of rice straw), and the sub plot was soil ameliorations (control, 120 kg/ha K2O, 750 kg/ha S, 5 t/ha gypsum, 5 t/ha manure, and 1.5 t/ha of gypsum + 5 t/ha manure). Results showed that mulching, and amelioration with 120 kg/ha K2O, 750 kg/ha S, 5 t/ha gypsum decreased soil EC, but could not improve groundnut growth and could not retard chlorophyll degradation because the soil was EC still high (12.5 dS/m). The higher yield (1.49 t/ha dry pods) can be obtained by amelioration with 750 kg sulphur/ha combined with mulching